The addition of lysolecithin to broiler diets improves growth performance across fat levels and sources: a meta-analysis of 33 trials. Issue 1 (2nd January 2020) - Wealleans, A. L.; Jansen, M.; di Benedetto, M.
ABSTRACT: 1. This study aimed to quantify the effect of fat type (including unsaturated to saturated ratio (U:S)) and increasing doses of lysolecithin-based products on nutrient availability and growth performance in broiler chickens. 2. A total of 33 separate experimental reports were collated according to predetermined selection criteria to provide 16 performance trials with 'on top' application, and 17 performance trials using reformulated diets, where the contribution of the lysolecithin was taken into account. Data on average daily gain (ADG) and body weight corrected FCR (FCRc) were analysed using the REML method with trial as a random effect. 3. Across the constituent trials, average added dietary fat and oil inclusion was 4.42% (min 1.15%, max 7.00%), with varied U:S ratio (min 0.94, avg 2.50, max 7.65), reflecting diverse fat sources. Overall, neither bird growth performance nor response to lysolecithin supplementation were significantly affected by the U:S ratio of the diets. 4. In performance trials where lysolecithin was added 'on top' of existing formulations, FCRc was significantly reduced by lysolecithin at 250 g/t inclusion compared to the control, with 125 g/t returning an intermediate value. In reformulated trials, FCRc was not significantly affected, suggesting lysolecithin supplementation at 125 and 250 g/t could recover average dietary energy reductions of 57.88 and 73.11 kcal/kg feed, respectively. 5. In conclusion, this study showed that the addition of lysolecithin at levels of 125 g/t and above to broiler diets consistently improved feed efficiency across a range of basal dietary ingredients and fat sources.